6+6+6+8+8=31 that's the answer to your problem
<u>Solution </u><u>1</u><u> </u><u>:</u><u>-</u>
Given expression ,
We know that,
Therefore , this can be written as ,
<u>Solution</u><u> </u><u>2</u><u>:</u><u>-</u>
Given expression ,
We know that,
Therefore, this can be written as ,
Answer:
huhhh i dont understand fully
Step-by-step explanation:
An=a1(r)^(n-1)
a1=first term
r=common rati
common ratio is a term divded by previous term
6/3=2
r=2
first term is 3
an=3(2)^(n-1)
14th term
a14=3(2)^(14-1)
a14=3(2)^13
a14=3(8192)
a14=24576
the 14th term is 24576
Answer: D 120%
Step-by-step explanation: